The Influence of Social Media Marketing Strategies on Consumer Repurchase Intention of Gluten-Free Food Products - Muhammad Rifqi Fadhlurrahman; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to analyze the influence of Social Media Marketing on Repurchase Intention by including Brand Love and Brand Loyalty as mediating variables in consumers of gluten-free Rq Cookies products. The phenomenon of the emergence of public awareness of a healthy lifestyle has encouraged the development of various gluten-free products in Indonesia, including those produced by the MSME Rq Cookies. To understand consumer behavior, this study uses a quantitative method through a survey of 152 respondents who have purchased Rq Cookies products and actively follow brand activities on social media such as Instagram and TikTok. Data analysis uses the SEM-PLS software. The results show that Social Media Marketing has a positive and significant influence on Brand Love, Brand Loyalty, and Repurchase Intention. However, Brand Love does not have a significant influence on Repurchase Intention and does not act as a mediator in the relationship between Social Media Marketing and Repurchase Intention. In contrast, Brand Loyalty is proven to have a significant influence on Repurchase Intention and is able to mediate the relationship. These findings indicate that loyalty plays a stronger role than emotional aspects in the context of repeat purchases of gluten-free products. The managerial implication is that Rq Cookies needs to strengthen its social media strategy by focusing on increasing brand loyalty through consistent, informative content that highlights the quality and health value of gluten-free products, including developing a community of consumers who care about a healthy lifestyle.